Availability of essential medicines for children with cancer in Sri Lanka: a prospective cohort study. (July 2022) - Gunasekera, Sanjeeva; Jayasinghe, Tithira; Somathilake, Mahendra; Ariyarathne, Yasantha; Lam, Catherine
Abstract: Background: The WHO Model List of Essential Medicines for children (2019 version) contains 39 antineoplastic and supportive medicines deemed essential for the successful treatment of children with cancer. The availability of these medicines varies across countries, but most reports are retrospective or short term. This study tracked the availability of these medicines in Sri Lanka's only treatment centre for childhood cancer, the National Cancer Institute of Sri Lanka, over 1 year, and examined initial mitigation strategies and implications. Methods: We prospectively tracked the availability of essential medicines at the National Cancer Institute of Sri Lanka in a customised database from April 1, 2019, to March 31, 2020. Consumption volumes and unit prices were extracted from the Sri Lankan Ministry of Health's Medical Supplies Management Information System. Availability was mapped against regimens used to treat childhood cancers, including WHO Global Initiative for Childhood Cancer index cancers, in Sri Lanka and by the International Society of Paediatric Oncology. Descriptive analyses and linear regression were used to assess factors associated with the unavailability of medicines. Findings: 31 (79%) of 39 medicines listed in the WHO Model List of Essential Medicines for children are in the Sri Lankan Essential Medicine List and 36 (92%) of 39 (48 formulations) are registered for use. Thioguanine, arsenic, and realgar-Indigo naturalis were the unregistered medicines. Over the study period, less than half (17 [44%]) of medicines were consistently available for 100% of the study period, 14 (36%) were available 75–100% of the study period, three (8%) between 50–75% of the study period, and two (5%) for less than 50% of the duration of the study period. The least available drug was procarbazine (available only on 212 [58%] of 366 days in the total study period). The availability of medicines did not reach 100% on any day in the study period. No substantial monthly variability was noted, but the best availability was in August, 2019, and the worst in January, 2020. Applying regimen-based analyses for acute lymphoblastic leukaemia, 12 stockout episodes affected seven (18%) medicines (median 37·5 consecutive days, IQR 12·0–62·0), whereas stockout mitigation strategies (low stock periods not resulting in stockout) were effective in 11 instances; only three (8%) medicines did not have alternate formulations or substitutions during stockouts (vincristine, cytarabine, and mercaptopurine). Of the WHO Global Initiative for Childhood Cancer index cancers, Hodgkin lymphoma was the most affected by stockouts, and retinoblastoma was the least affected. Annual consumption volumes (p=0·13), unit cost (p=0·5), and annual costs per medicine (p=0·091) were not significantly associated with medicine unavailability. Interpretation: Non-availability of essential medicines is an important problem to be addressed for children with cancer in Sri Lanka. This study showed the feasibility of prospective essential medicines tracking at the point-of-care, and how data visibility can inform stock and inventory management and help to identify mitigation strategies for stockouts. Funding: None.